Caspase-10-dependent cell death in Fas/CD95 signalling is not abrogated by caspase inhibitor zVAD-fmk. - Elodie Lafont; Delphine Milhas; Justin Teissié; Nicole Therville; Nathalie Andrieu-Abadie; Thierry Levade; Hervé Benoist; Bruno Ségui (PLoS ONE, 2010)
BACKGROUND: Upon CD95/Fas ligation, the initiator caspase-8 is known to activate effector caspases leading to apoptosis. In the presence of zVAD-fmk, a broad-spectrum caspase inhibitor, Fas engagement can also trigger an alternative, non-apoptotic caspase-independent form of cell death, which is initiated by RIP1. Controversy exists as to the ability of caspase-10 to mediate cell death in response to FasL (CD95L or CD178). Herein, the role of caspase-10 in FasL-induced cell death has been re-evaluated. METHODOLOGY AND PRINCIPAL FINDINGS: The present study shows that FasL-induced cell death was completely impaired in caspase-8- and caspase-10-doubly deficient (I9-2e) Jurkat leukaemia T-cell lines. Over-expressing of either caspase-8 or caspase-10 in I9-2e cells triggered cell death and restored sensitivity to FasL, further arguing for a role of both initiator caspases in Fas apoptotic signalling. In the presence of zVAD-fmk, FasL triggered an alternative form of cell death similarly in wild-type (A3) and in caspase-8-deficient Jurkat cells expressing endogenous caspase-10 (clone I9-2d). Cell death initiated by Fas stimulation in the presence of zVAD-fmk was abrogated in I9-2e cells as well as in HeLa cells, which did not express endogenous caspase-10, indicating that caspase-10 somewhat participates in this alternative form of cell death. Noteworthy, ectopic expression of caspase-10 in I9-2e and HeLa cells restored the ability of FasL to trigger cell death in the presence of zVAD-fmk. As a matter of fact, FasL-triggered caspase-10 processing still occurred in the presence of zVAD-fmk. CONCLUSIONS AND SIGNIFICANCE: Altogether, these data provide genetic evidence for the involvement of initiator caspase-10 in FasL-induced cell death and indicate that zVAD-fmk does not abrogate caspase-10 processing and cytotoxicity in Fas signalling. Our study also questions the existence of an alternative caspase-independent cell death pathway in Fas signalling.